2017
DOI: 10.3947/ic.2017.49.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Experimental Murine Peritonitis Model with Hog Gastric Mucin for Carbapenem-Resistant Gram-Negative Bacteria

Abstract: Animal models are essential to studies of infectious diseases. The use of mice to test bacterial infection has been extensively reported. However, methods applied to clinical isolates, particularly for carbapenem-resistant bacteria, must be tailored according to the infection models and bacteria used. In this study, we infected 6-week-old female BALB/c mice intraperitoneally with different strains of resistant bacteria plus 3% hog gastric mucin. This method was found to be efficient and readily applicable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…Female BALB/c mice were infected systemically with a lethal dose of NDM-HK in the presence of 2% mucin. Mucin is the macromolecular component of mammalian mucus, and commixture of mucin is used to enhance the bacterial pathogenicity in mouse peritoneal cavity 28 , 45 , whereas mice showed no morbidity or mortality when mucin was used alone. The infected mice were then administrated with a vehicle control, MER or CBS monotherapy or combination therapy, 4 h post infection, followed by twice-daily treatment via i.p.…”
Section: Resultsmentioning
confidence: 99%
“…Female BALB/c mice were infected systemically with a lethal dose of NDM-HK in the presence of 2% mucin. Mucin is the macromolecular component of mammalian mucus, and commixture of mucin is used to enhance the bacterial pathogenicity in mouse peritoneal cavity 28 , 45 , whereas mice showed no morbidity or mortality when mucin was used alone. The infected mice were then administrated with a vehicle control, MER or CBS monotherapy or combination therapy, 4 h post infection, followed by twice-daily treatment via i.p.…”
Section: Resultsmentioning
confidence: 99%
“…infection with A. baumannii strains of different virulence. Several laboratories have used porcine mucin to enhance the virulence of various A. baumannii clinical and type strains in mice (13,21,(24)(25)(26)(27). In this study, we assessed the relative virulence of 3 A. baumannii strains (ATCC 19606 T , ATCC 17961, and LAC-4) by the inclusion of mucin in the inocula.…”
Section: Resultsmentioning
confidence: 99%
“…1D), suggesting that the mucin-enhanced virulence in A. baumannii is not restricted to BALB/c mice. In this regard, other mouse strains, such as ICR-Swiss, Swiss White, and CF-1, previously have been used in similar models (16,18,19,26), although actual magnitudes of the enhancement in some of those studies had not been reported in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Many reports have suggested that bacteria can exploit mucin secreted by the human mucosa to survive and escape host defence systems . It is well known that a lethal dose of various bacteria in animal experimental models can be reduced when mucin is added to bacteria .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that a lethal dose of various bacteria in animal experimental models can be reduced when mucin is added to bacteria . It has also been shown that a 3% mucin solution from porcine stomach was enough to increase the virulence of E. coli , Klebsiella pneumoniae, Pseudomonas aeruginosa and Acinetobacter baumannii in a mouse peritonitis model . Salmonella enterica serovar Typhi enhanced its virulence in a murine model of infection .…”
Section: Discussionmentioning
confidence: 99%